2003
DOI: 10.1128/aem.69.5.2842-2847.2003
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and Enumeration of Cryptosporidium parvum from Animal Fecal Matrices

Abstract: Accurate quantification of Cryptosporidium parvum oocysts in animal fecal deposits on land is an essential starting point for estimating watershed C. parvum loads. Due to the general poor performance and variable recovery efficiency of existing enumeration methods, protocols were devised based on initial dispersion of oocysts from feces by vortexing in 2 mM tetrasodium pyrophosphate, followed by immunomagnetic separation. The protocols were validated by using an internal control seed preparation to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 21 publications
4
27
0
1
Order By: Relevance
“…The findings in this study showed higher detection of infectious agents in stool including Cryptosporidium in 6 samples, yeasts in 24 samples and B. hominis in 1 sample (Figure 2). These findings are consistent with the scientific reports of Davies et al (2003) and Weber et al (1992) on this technique as indicated by the extra detection of 7% and 10% of Cryptosporidium and yeasts, respectively (Figure 3).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The findings in this study showed higher detection of infectious agents in stool including Cryptosporidium in 6 samples, yeasts in 24 samples and B. hominis in 1 sample (Figure 2). These findings are consistent with the scientific reports of Davies et al (2003) and Weber et al (1992) on this technique as indicated by the extra detection of 7% and 10% of Cryptosporidium and yeasts, respectively (Figure 3).…”
Section: Discussionsupporting
confidence: 82%
“…Studies have shown that this method is efficient in the detection of parasites even when they appear in low numbers in a specimen (Weber et al, 1992;Davies et al, 2003;Cheesbrough, 2005). The findings in this study showed higher detection of infectious agents in stool including Cryptosporidium in 6 samples, yeasts in 24 samples and B. hominis in 1 sample (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…A 0.5-g aliquot of the fecal sample was weighed into a sterile 50-ml centrifuge tube. Diethyl ether was used in dispersal and defatting of calf fecal samples as described by Davies et al (9). To quantify recovery efficiency, each individual sample was seeded with ColorSeed (Biotechnology Frontiers Ltd.…”
Section: Methodsmentioning
confidence: 99%
“…Ltd., Castle Hill, NSW, Australia). The membranes were mounted on glass slides and scanned at ϫ250 magnification as described by Davies et al (14). Runoff samples from the pat experiments generally did not require concentration by ultrafiltration, but portions (10 ml) of these samples were assayed directly by IMS.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are difficulties associated with estimating the prevalence of pathogen infections in animals. These problems include whether to sample animals or their scats (25), how to calculate pathogen concentrations and prevalence from fecal pat data (12), and the detection limits of the methods used for enumeration (14,40).…”
mentioning
confidence: 99%